Management of psoriatic arthritis (PsA) - Coates, Laura (Henry Stewart Talks, 2021)
Assessment of comorbidities, Individualising treatment, The multiple domains of PsA, Current, upcoming, and ineffective therapies, Treatment strategy, Prompt and rapid review